Multimodal Analgesic Regimen for Spine Surgery: A Randomized Placebo-controlled Trial. (May 2020) - Maheshwari, Kamal; Avitsian, Rafi; Sessler, Daniel I.; Makarova, Natalya; Tanios, Marianne; Raza, Syed; Traul, David; Rajan, Shobana; Manlapaz, Mariel; Machado, Sandra; Krishnaney, Ajit; Machado, Andre; et al.
Abstract : Background: Various multimodal analgesic approaches have been proposed for spine surgery. The authors evaluated the effect of using a combination of four nonopioid analgesics versus placebo on Quality of Recovery, postoperative opioid consumption, and pain scores. Methods: Adults having multilevel spine surgery who were at high risk for postoperative pain were double-blind randomized to placebos or the combination of single preoperative oral doses of acetaminophen 1, 000 mg and gabapentin 600 mg, an infusion of ketamine 5 µg/kg/min throughout surgery, and an infusion of lidocaine 1.5 mg/kg/h intraoperatively and during the initial hour of recovery. Postoperative analgesia included acetaminophen, gabapentin, and opioids. The primary outcome was the Quality of Recovery 15-questionnaire (0 to 150 points, with 15% considered to be a clinically important difference) assessed on the third postoperative day. Secondary outcomes were opioid use in morphine equivalents (with 20% considered to be a clinically important change) and verbal-response pain scores (0 to 10, with a 1-point change considered important) over the initial postoperative 48 h. Results: The trial was stopped early for futility per a priori guidelines. The average duration ± SD of surgery was 5.4 ± 2.1 h. The mean ± SD Quality of Recovery score was 109 ± 25 in the pathway patients (n = 150) versus 109 ± 23 in the placebo group (n = 149); estimated difference in means was 0 (95% CI, –6 to 6, P = 0.920). Pain management within the initial 48 postoperative hours was not superior in analgesic pathway group: 48-h opioid consumption median (Q1, Q3) was 72 (48, 113) mg in the analgesic pathway group and 75 (50, 152) mg in the placebo group, with the difference in medians being –9 (97.5% CI, –23 to 5, P = 0.175) mg. Mean 48-h pain scores were 4.8 ± 1.8 in the analgesic pathway group versus 5.2 ± 1.9 in the placebo group, with the difference in means being –0.4 (97.5% CI; –0.8, 0.1, P = 0.094). Conclusions: An analgesic pathway based on preoperative acetaminophen and gabapentin, combined with intraoperative infusions of lidocaine and ketamine, did not improve recovery in patients who had multilevel spine surgery. Abstract : Adult spine surgery patients were randomized to placebo or to the combination of acetaminophen, gabapentin, ketamine, and lidocaine. The quality of recovery was similar in each group, as were pain scores and opioid consumption.Supplemental Digital Content is available in the text.